2011
DOI: 10.1111/j.1365-2923.2011.04075.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the reliability of objective structured clinical examination scores

Abstract: CONTEXT The objective structured clinical examination (OSCE) is comprised of a series of simulations used to assess the skill of medical practitioners in the diagnosis and treatment of patients. It is often used in high-stakes examinations and therefore it is important to assess its reliability and validity.METHODS The published literature was searched (PsycINFO, PubMed) for OSCE reliability estimates (coefficient alpha and generalisability coefficients) computed either across stations or across items within s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
193
2
17

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(241 citation statements)
references
References 51 publications
13
193
2
17
Order By: Relevance
“…Although these leniency and stringency variations might be a potential issue in communication-related stations, 4,5,17,18 which are generally not dependent on fact (compared with a discipline such as anatomy for which an answer is either correct or not), we did not find a statistical difference in absolute scores between examiners and the content area being examined. In some undergraduate and postgraduate examinations, the use of 2 examiners per scenario is encouraged to minimize inter-examiner variation, though many examinations now rely on just 1 examiner for each OSCE station.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Although these leniency and stringency variations might be a potential issue in communication-related stations, 4,5,17,18 which are generally not dependent on fact (compared with a discipline such as anatomy for which an answer is either correct or not), we did not find a statistical difference in absolute scores between examiners and the content area being examined. In some undergraduate and postgraduate examinations, the use of 2 examiners per scenario is encouraged to minimize inter-examiner variation, though many examinations now rely on just 1 examiner for each OSCE station.…”
Section: Discussionmentioning
confidence: 41%
“…17 In addition to the reasons discussed earlier, recent work using a NASA task load index rating, identified that excessive workloads occur in OSCE examiners in a similar way that is seen in other professions such as airline pilots. 20 Further research is needed in this relatively unexplored area and other ways to minimize examiner variables need to be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the number of stations, and rater could be effective for improving the reliability of objective structure exams. 53 The other studies showed that with transparent objectives, developed standardized assessment checklist and proper rater training could be improved the ITOSCE reliability.…”
Section: Reliability Indicatorsmentioning
confidence: 99%
“…This is based on the global standards proposed by the World Federation for Medical Education (1,2). Cross-sectional studies for each period have been reported regarding education at the pre-graduate clinical practical training and post-graduate clinical training levels (3)(4)(5)(6)(7)(8)(9). However, no studies on a clinical competency examination as an overall evaluation at the end of pregraduate clinical practical training and at the end of OSCAT as a pilot study with the objective of establishing a clinical competency evaluation for professionalism in dental education.…”
Section: Introductionmentioning
confidence: 99%